2015
DOI: 10.1161/atvbaha.115.306251
|View full text |Cite
|
Sign up to set email alerts
|

Neoatherosclerosis From a Pathologist’s Point of View

Abstract: Figure 2. Progression of neoatherosclerosis occurring within drug-eluting stent (DES).A and B, Low-and high-power images of early atherosclerotic change characterized by luminal foam cells (arrows) with underlying fibrointimal thickening. C and D, Low-and high-power images of foamy macrophage clusters (arrows) in the peristrut region adjacent to luminal surface. E and F, Low-and high-power images of fibroatheroma with necrotic core (NC) within neointima. G and H, Low-and high-power images of thin cap fibroathe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 46 publications
0
14
0
2
Order By: Relevance
“…5 In our study, calcification was the most frequent component of neoatherosclerosis in the in-scaffold segment rather than in the out-scaffold segment 5 mm adjacent to the edge of the neointima. 24 OCT enables the best characterization of neointimal tissue within stents due to its superior axial resolution (10-20 μm). For quantitative OCT analysis, neoatherosclerosis is defined as lipid-laden plaque including thin-cap fibroatheroma (TCFA) with or without intimal rupture and/or thrombus, and/or calcific plaque with or without neovascularization and/or macrophages.…”
Section: Neoatherosclerosis Of Absorb Bvsmentioning
confidence: 99%
“…5 In our study, calcification was the most frequent component of neoatherosclerosis in the in-scaffold segment rather than in the out-scaffold segment 5 mm adjacent to the edge of the neointima. 24 OCT enables the best characterization of neointimal tissue within stents due to its superior axial resolution (10-20 μm). For quantitative OCT analysis, neoatherosclerosis is defined as lipid-laden plaque including thin-cap fibroatheroma (TCFA) with or without intimal rupture and/or thrombus, and/or calcific plaque with or without neovascularization and/or macrophages.…”
Section: Neoatherosclerosis Of Absorb Bvsmentioning
confidence: 99%
“…Although this could not be studied because of small numbers of cases, different neointimal patterns may reflect different underlying mechanisms of development of NA. NA in BMS is typically manifested as a lipid pool in a well-developed neointima, which is rich in vascular smooth muscle cells, and apoptosis of vascular smooth muscle cells is believed to be the underlying cause of NA [31]. However, NA in DES is considered to be a direct consequence of delayed artery healing with macrophage infiltration and apoptosis.…”
Section: Progression To Neoatherosclerosismentioning
confidence: 99%
“…Emerging evidence suggests chronic inflammation and/or incompetent endothelium as important contributors to this pathological change within stent (54,55). Recent studies demonstrated that neoatherosclerosis could be developed in late phase after both bare metal stent (BMS) and drugeluting stent (DES) implantation (56,57).…”
Section: In-stent Neoatherosclerosismentioning
confidence: 99%
“…In addition, earlier and more frequent development of neoatherosclerosis after DES implantation has been observed in pathohistological and clinical studies (58,59). Currently, neoatherosclerosis is considered as one of important mechanisms associated with late stent thrombosis and restenosis (54,57,60,61). OCT has a great potential to evaluate in-stent neoatherosclerosis in vivo.…”
Section: In-stent Neoatherosclerosismentioning
confidence: 99%